Tecnologia assistiva: um teclado virtual evolutivo para aplicação em sistemas de comunicação alternativa e aumentativa - Loja, Luiz Fernando Batista (2015)
People withmobilityandspeechrestrictionssimultaneoushaveverbalcommunicationandbody language impaired.Inthemostextremecasesthepatientsaredeprivedofalltheirmovements and speechcapabilities.ThissituationischaracterizedastheLocked-inSyndrome(LIS).The augmentativeandalternativecommunicationtechnologiesprovidemethodsandsoftwaresthat allowthesepatientstocommunicatewiththeexternalenvironmentandpeoplearoundthem. Among thevariousmethodsandexistingcommunicationprogramswecanhighlightthevirtual keyboard.However,datainputusingthiskindofkeyboardisconsiderablyslowerandmore tiresome forpeoplewithLIS.Thisworkaimstobuildanassistivevirtualkeyboardtoassist patients withseveremobilityrestrictionsandspeechtocommunicate.Toachievethisgoalit wasconductedtwosystematicreviewsandaliteraturereview.Fromtheknowledgegained from theseresearchswemodeledanddevelopedanassistivevirtualkeyboard.Moreover,we designed andimplementedanevolutionarymethodologythatallowsthekeyboardtoadaptitself to user svocabularyandwritingmode.Finally,anexperimentthatcomparesthetraditional method keyboardsoptimizationwiththemethodologyproposedinthisthesiswascarriedout.